Mothers' birth giving status and the division of parental leave: A comparison of adoptive and biological parents - Ylva Moberg; Maaike Van der Vleuten (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2022)
Mothers' longer time on parental leave after having children has been proposed as one reason for remaining gender inequalities in the labor market. This paper investigates the determinants of the unequal division of parental leave, specifically the argument that mothers take more parental leave as a consequence of pregnancy and breastfeeding. We compare the division of parental leave of biological parents (where the mother gave birth) to adoptive parents (where she did not), to assess to what extend the unequal division of childcare responsibilities can be explained by the physiological aspects of biological motherhood. We analyze Swedish register data on couples who had their first biological or adopted child in 1994 - 2009, and families that had both adopted and biological children. We find that the mother's share of parental leave is lower if the child is adopted. The difference is small, 80% versus 82%, although statistically significant. We thus conclude that going through a pregnancy increases the mothers initial parental leave, but the impact is minor. Instead, our results indicate that gender norms of mothers as caregivers and fathers as breadwinners is more likely to explain (at least part of) couples' division of parental leave.
Keywords: D13; J13; J16; J22; 330; parental leave; gender norms; motherhood; division of labor